Performance Analysis of Duty-Cycle Division Multiplexing for Optical Fiber Communication Systems - Mahdiraji, Ghafour Amouzad (2009)
The ever increasing demand for network capacity motivates the explorations for new modulation formats and multiplexing techniques. Wavelength division multiplexing (WDM) channel capacity can be improved by using time division multiplexing (TDM). However, TDM requires precise bit and symbol synchronization and limited from the operating speed of electronic components. The introduction of return-tozero (RZ) line coding facilitates TDM synchronization in high speed transmission systems. Alternatively WDM channel capacity can be doubled by using polarization division multiplexing (PDM) or differential quadrature phase-shift-keying (DQPSK) modulation format. Duty-cycle division multiplexing (DCDM) is another multiplexing technique that can support multiple users per WDM channel. Previously, initial version of DCDM (IVDCDM) is proposed for optical fiber communications. DCDM takes advantage of RZ and offers even better synchronization at the lower clock frequency with smaller spectral width. However, IV-DCDM is badly affected from the fiber chromatic dispersion (CD). In addition, it requires high optical signal-to-noise ratio (OSNR) and less tolerance to self-phase modulation (SPM). For implementation, the IV-DCDM architecture required n modulators for n channels at the multiplexer and n + 1 sampling circuits at the receiver, which is not economically efficient. In this study, the design of DCDM multiplexer and demultiplexer is improved. A new set of algorithm are developed for data recovery in the receiver. At the same time, a model for BER estimation based on the decision algorithms is established. Performance of the proposed demultiplexer with the new decision algorithm is evaluated using the same multiplexer design used in IV-DCDM. Since in the improve setup the multiplexer operates in optical domain this system is referred to as O-DCDM. Using the O-DCDM, performance of IV-DCDM is improved significantly by around 40 times in terms of CD tolerance, 6.5 dB better OSNR and around 3 dB higher SPM threshold. The number of sampling circuits is also reduced by one count in the proposed demultiplexer, which leads towards design simplification. Performance of the proposed multiplexer architecture is evaluated together with the proposed demultiplexer. Since the proposed multiplexer operates in electrical domain this system is referred to as E-DCDM. Using the E-DCDM, the numbers of required modulators are reduced to only one regardless of the number of user. Using EDCDM, performance of IV-DCDM is improved by around 48 times in terms of CD tolerance, 1.6 dB better OSNR and around 4.5 dB higher SPM threshold. Performance of E-DCDM is improved further by using amplitude distribution controller (ADC). Using E-DCDM with ADC, referring to IV-DCDM, performance is improved by around 46 times in CD tolerance, 7.5 dB better OSNR and 3.5 dB more SPM threshold. Based on these developments, performance of DCDM is comparable against the available multiplexing and modulation techniques with an advantage, which is simpler transmitter and receiver. DCDM can support multiple users per WDM channel without the needs of increasing the clock rate at the receiver. Using this technique, 7 × 10 Gb/s is transmitted over 139 km and recovered by using 10 GHz clock.